Effect of thermoplastic polyurethane on properties of polyvinyl chloride in designing bedpan
Commercialized bedpan made from hard plastic gives discomfort to the patients. The study was perform to improved. The present study determines the mechanical, physical and thermal properties of TPU/PVC blend in order to be used as material to fabricate a bedpan. TPU and PVC were mixed by melt-mixing method and were undergoing hot press compression molding to make a sample. The samples of PVC/TPU with ratio 90/10, 70/30 and 50/50 were subjected to tensile, water absorption, chemical resistance, Scaning Electron Microscopic (SEM), Thermal Gravimetric Analysis (TGA) and Differential Scanning Calorimetric (DSC) test. The simulation analysis using ANSYS workbench software was performed at the end of test. 50TPU was chosen as the best ratio of TPU/PVC blend because they have good tensile strength, lower modulus and high elasticity. The blending of TPU and PVC has decreased the percentage of water absorption of TPU since TPU has highest water gain due to hydrophilic nature and PVC has hydrophobic nature. Hydrochloric acid (HCl) had a stronger effect on TPU/PVC blend compared to sodium hydroxide (NaOH) for all blend compositions for chemical resistance test. The result of SEM micrograph shows that the sample became smoother when more TPU was added. The 50TPU sample exhibits smoother surface and cluster of blend on its surface diminish when increasing TPU content. TGA result shows that the decomposition occur in two stage for TPU/PVC blend. The decomposition of PVC was lower than TPU and higher than TPU/PVC blend. Based on DSC result, TPU/PVC blend revealed one transitions melting temperature (Tm) formed for sample of 10TPU, 30TPU and 50TPU.